Energy mass balance and flow modeling of early Holocene glaciers in the Queshque valley, Cordillera Blanca, Peru. (1st April 2022) - Stansell, Nathan D.; Mark, Bryan G.; Licciardi, Joseph M.; Rodbell, Donald T.; Fairman, Jonathan G.; Schoessow, Forrest S.; Shutkin, Tal Y.; Sorensen, Mary
Abstract: Our limited knowledge of the timing and pattern of early Holocene climate variability in the tropical Andes hinders our ability to evaluate any potential linkages between low and high latitude oceanic-atmospheric dynamics. There is mounting evidence that glaciers in the Peruvian Andes stabilized at times during the early Holocene, suggesting there were periods of colder and/or wetter conditions that interrupted an overall pattern of a warmer and drier climate. Evaluating the global significance of these glacial fluctuations requires that the nature of these apparent cooling events and any shifts in the hydrologic cycle be better quantified. Here we apply a physically-based glacier model to reconstruct and interpret early Holocene-aged paleoglaciers in steady-state with a range of tropical climatic conditions in the Queshque valley of the Cordillera Blanca, Peru (9.8°S). This model uses a LiDAR-based digital elevation model (DEM) and hourly meteorological data as inputs to calculate the fully-distributed surface energy and mass balance (SEMB). This approach allows us to better capture the diurnal range of environmental variability at a spatial resolution that has not been achieved with previous paleo-glacier modeling efforts in this region. A 3-D rendition of paleoglaciers was then developed based on a flow model that responds to the SEMB input, accounting for the valley topography. The model was validated by simulating glaciers that match both field and satellite observations of modern glacier area limits, as well as ice thicknesses that are consistent with recently measured ground-penetrating radar (GPR) profiles of the main glacier tongue. After adjusting for changes in early Holocene global radiation values, and using regional paleoclimate records as constraints for the model, the maximum early Holocene ice limit in the valley dating to ∼10.8 (±0.1) ka was reconstructed using a 3.0 °C cooling and a 25% increase in precipitation relative to today. An up-valley ice extent dating to ∼9.4 (±0.3) ka was reconstructed using a 2.8 °C cooling and no change in precipitation amounts relative to today. These results suggest that conditions were cold and wet enough to maintain glaciers at times during the early Holocene, even though a shift to drier conditions combined with modestly warmer temperatures drove a phase of ice retreat from at least ∼10.8 to ∼9.4 ka. These results suggest that southern tropical temperatures and the hydrologic cycle rapidly reorganized during the early Holocene in conjunction with diminishing ice sheets and shifting environmental conditions in the high latitudes. Highlights: We present a new approach for modeling tropical paleo-glaciers. Glaciers in the Cordillera Blanca stabilized at times during the early Holocene. Glacial stillstands occurred during briefly colder and wetter conditions. Ice retreat occurred when it was warmer and drier. Early Holocene glaciers were sensitive to both temperature and precipitation.